Making Decisions About Medications in Critically Ill Children. Issue 1 (January 2015) - Duffett, Mark; Choong, Karen; Vanniyasingam, Thuva; Thabane, Lehana; Cook, Deborah J.
<x xml:space="preserve">Abstract</x> Objective: Changing clinician practice in pediatric critical care is often difficult. Tailored knowledge translation interventions may be more effective than other types of interventions. To inform the design of tailored interventions, the primary objective of this survey was to describe the importance of specific factors that influence physicians and pharmacists when they make decisions about medications in critically ill children. Design: In this postal survey, respondents used 7-point scales to rate the importance of specific factors that influence their decisions in the following scenarios: corticosteroids for shock, intensive insulin therapy, stress ulcer prophylaxis, surfactant for acute respiratory distress syndrome, and sedation interruption. We used generalized estimating equations to examine the association between the importance of specific factors influencing decision making and the scenario and respondents' practice, views, and demographics. Setting: Canadian PICUs. Participants: One hundred and seventeen physicians and pharmacists practicing in 18 PICUs. Interventions: None. Measurements and Main Results: The response rate was 61%. The three factors reported to most strongly influence clinician decision making overall were: severity of illness (mean [SD] 5.8 [1.8]), physiologic rationale (5.2 [1.3]), and adverse effects (5.1 [1.9]). Factors least likely to influence decision making were drug costs (2.0 [1.5]), unit policies (2.9 [1.9]), and non–critical care randomized controlled trials (3.1 [1.9]). The relative importance of 8 of the 10 factors varied significantly among the five scenarios: only randomized controlled trials in critically ill children and other clinical research did not vary. Clinician characteristics associated with the greatest difference in importance ratings were: frequent use of the intervention in that scenario (seven factors), profession (five factors), and respondents' assessment of the quality of evidence (five factors). Conclusions: The relative importance of many factors that clinicians consider when making decisions about medications varies by demographics, and depends on the clinical problem. This variability should be considered in quality improvement and knowledge translation interventions in this setting.